2012
DOI: 10.1002/cite.201100255
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Drugs in Soil and in the Aquatic Environment

Abstract: In den letzten Jahren wurden weltweit Untersuchungen zu Vorkommen, Verhalten und möglichen Effekten von Tierarzneimitteln in der Umwelt durchgeführt. Der nach wie vor beträchtliche Einsatz von Tierarzneimitteln in der intensiven Tierhaltung führt vor allem zu einem Eintrag von pharmakologisch wirksamen Stoffen und ihren Metaboliten in Wirtschaftsdünger. Durch die Düngung gelangen diese in Böden und evtl. auch in das Grundwasser. Akute toxische Effekte auf Umweltorganismen durch bestimmte Antiparasitika sind be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
9
0
10
Order By: Relevance
“…Hartlieb et al (2003) demonstrated that a substantial fraction of the contaminants is locked up within the organic matrix by formation of non-extractable residues (NER). First results indicate that the anaerobic digestion process is also not able to degrade antibiotics completely, and the degradation efficiency may vary from very low elimination to up to 99 % (Hamscher and Mohring 2012). The process temperature is of high importance for the reduction of antibiotics and coliforms: Varel et al (2012) found higher CTC degradation and removement of coliforms during anaerobic digestion when the process temperature was raised from 22 to 38 or 55°C.…”
Section: Contamination Of Organic P Fertilizers By Antibiotics and Edcsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hartlieb et al (2003) demonstrated that a substantial fraction of the contaminants is locked up within the organic matrix by formation of non-extractable residues (NER). First results indicate that the anaerobic digestion process is also not able to degrade antibiotics completely, and the degradation efficiency may vary from very low elimination to up to 99 % (Hamscher and Mohring 2012). The process temperature is of high importance for the reduction of antibiotics and coliforms: Varel et al (2012) found higher CTC degradation and removement of coliforms during anaerobic digestion when the process temperature was raised from 22 to 38 or 55°C.…”
Section: Contamination Of Organic P Fertilizers By Antibiotics and Edcsmentioning
confidence: 97%
“…Nevertheless Hamscher and Mohring (2012) could demonstrate that-despite strong sorption-significant amounts of TCs were transferred to the groundwater with a maximum concentration of 0.13 µg l −1 . Even higher concentrations were detected in surface waters (CTC: 0.11-0.69 µg l −1 , oxytetracycline: 0.15-1.34 µg l −1 ) contaminated by run-off from agricultural sites (Hamscher and Mohring 2012).…”
Section: Effects Of Antibiotics In the Environment Shown Exemplary Fomentioning
confidence: 98%
See 1 more Smart Citation
“…Most antibiotics are water-soluble (e.g. Tetracyclines (TCs) and sulfonamides were found at a magnitude of mg kg −1 in manure after designated use; tylosin, salinomycin and tiamulin were found in lower concentrations of µg kg −1 (Hamscher and Mohring 2012). tetracyclines and ß-lactam antibiotics) or metabolites (e.g.…”
Section: Excretion Of Antibioticsmentioning
confidence: 99%
“…Im Abb. 3: Forschungsaktivitäten ( → ) der AG Hamscher im Bereich "( Tier )Arzneimittel in der Umwelt" ( modifiziert nach [13] ).…”
Section: Ag Hamscher -Rückstands-und Umweltanalytikunclassified